PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SUKA MANDIRI GARMENT DI KOTA TANGERANG SELATAN - Diki Setiawan; Siti Aesah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine the Effect of Physical Work Environment and Work Discipline on Employee Performance at PT Suka Mandiri Garment in South Tangerang City, both partially and simultaneously. This type of research uses a descriptive quantitative method using a saturated sampling technique of 61 people. Data analysis techniques use data instrument tests, classical assumption tests, linear regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of the analysis show that the physical work environment has a significant effect on employee performance with a regression equation of Y = 11.848 + 0.738X1, with a correlation coefficient value of 0.627 meaning that the physical work environment variable has a strong level of influence and a determination value of 39.3%, and with a sig value of 0.001 <0.05, the hypothesis test obtained a t-value of 6.175 > t-table 2.002. Work discipline has a significant effect on employee performance with the regression equation Y = 16.073 +0.557X2, with a correlation coefficient value of 0.531 meaning that the work discipline variable has a strong level of influence and a determination value of 28.2% and with a sig value of 0.00 <0.05, the hypothesis test obtained a t count value of 4.811> t table 2.002. The physical work environment and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 9.798 +0.577X1 +0.217X2, with a correlation coefficient value of 0.645 meaning that the physical work environment and work discipline variables have a strong level of influence and a determination value of 41.7% and with a sig value of 0.00 <0.05, the hypothesis test obtained a f count value of 20.706> ft table 3.156. Thus it is proven that H0 is rejected and Ha is accepted.